2019
DOI: 10.3390/cells8101288
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous and Visceral Adipose-Derived Mesenchymal Stem Cells: Commonality and Diversity

Abstract: Adipose-derived mesenchymal stem cells (ASCs) are considered to be a useful tool for regenerative medicine, owing to their capabilities in differentiation, self-renewal, and immunomodulation. These cells have become a focus in the clinical setting due to their abundance and easy isolation. However, ASCs from different depots are not well characterized. Here, we analyzed the functional similarities and differences of subcutaneous and visceral ASCs. Subcutaneous ASCs have an extraordinarily directed mode of moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 68 publications
2
31
0
Order By: Relevance
“…Moreover, the clinical efficacy of ADSCs remains dependent of the number of cells injected their route of administration and their location's origin as well. Visceral ADSCs secrete higher quantities of inflammatory cytokines IL-6, IL-8 and TNF-α when compared to the subcutaneous one's [72].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the clinical efficacy of ADSCs remains dependent of the number of cells injected their route of administration and their location's origin as well. Visceral ADSCs secrete higher quantities of inflammatory cytokines IL-6, IL-8 and TNF-α when compared to the subcutaneous one's [72].…”
Section: Resultsmentioning
confidence: 97%
“…The impact of microenvironment changing on ADSCs functionality, on their induction of proliferation, differentiation and migration has already been reported [32][33][34][35]72]. Reciprocally, ADSCs are reported to address this microenvironment in vitro, their conditioned media was reported to activate macrophages and to increase the secretion of TNF and IL-10 anti-inflammatory cytokines stimulating thus wound healing [37,73].…”
Section: Immunoregulatory Effects Of Adscs In Skinmentioning
confidence: 93%
“…The MSC characteristics can vary depending on the site of tissue harvest [16]. Reports demonstrate differences in MSC characteristics when comparing subcutaneous and visceral adipose tissue surrounding female reproductive tissue obtained during Caesarean section [17,18]. Ritter et al concluded that human visceral fat associated with the reproductive organs had a higher potential to differentiate into adipogenic and osteogenic cells and secreted higher levels of inflammatory cytokines, emphasizing the importance of the site of tissue harvest [17].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue covers research articles investigating various adipose tissues as a source for ASC isolation [ 1 , 2 , 3 ], specific cultures methods to enhance proliferation or viability [ 4 , 5 , 6 , 7 ], and the differentiation capacity [ 8 , 9 , 10 , 11 , 12 ]. Furthermore, other studies highlight aspects of various diseases [ 13 , 14 ], the immunosuppressive potential of ASCs and their derivates [ 15 ] or the in vivo tracking of transplanted ASCs [ 16 ].…”
mentioning
confidence: 99%
“…Ritter and co-workers analyzed the functional similarities and differences of ASCs isolated from different adipose depots [ 3 ]. The authors described that ASCs isolated from subcutaneous and visceral fat share multiple cellular features, but significantly differ in their functions.…”
mentioning
confidence: 99%